Levodopa/Carbidopa Intestinal Gel Long‐Term Outcome in Parkinson's Disease: Focus on Dyskinesia. Issue 8 (18th September 2020) - Fabbri, Margherita; Zibetti, Maurizio; Calandra‐Buonaura, Giovanna; Contin, Manuela; Sambati, Luisa; Mohamed, Susan; Romagnolo, Alberto; Berchialla, Paola; Imbalzano, Gabriele; Giannini, Giulia; Rizzone, Mario G.; Artusi, Carlo Alberto; et al.
ABSTRACT: Background: Levodopa‐carbidopa intestinal gel (LCIG) treatment has shown variable effect on dyskinesia in Parkinson's disease (PD). Objective: To identify PD patients who are likely to have troublesome dyskinesia under LCIG treatment and describe the pharmacokinetic‐dynamic profile and dyskinesia phenomenology of those patients. Methods: PD patients were assessed for clinical and therapeutic variables, before LCIG treatment ( T0 ) and at last outpatient visit ( T1 ). Sub‐groups of patients with and without "troublesome dyskinesia" (UPDRS IV, item 33 ≥2), matched for disease and LCIG treatment duration, underwent a pharmacokinetic‐dynamic assessment. Results: We included 53 PD patients. After a mean of 51.7 ± 34.1 months of LCIG treatment, "off‐time" was significantly reduced, whereas, dyskinesia duration/disability did not change. The multivariate regression model, adjusted for LCIG treatment duration, showed that being female increases the risk of presenting troublesome dyskinesia at T1 (odds ratio [OR] = 9.2; 95% confidence interval [CI] = 2.4–37.4) that was also significantly associated to longer off periods at T1 (OR= 4.4; 95% CI = 1.1–14.3). Female patients showed a higher risk for a higher dyskinesia score at T1 (sum of the items 32 and 33: P = 0.001). Patients with troublesome dyskinesia showed a tendency for a lower motor benefit and the appearance of more severe dyskinesia despite similar levodopa plasma concentration. Conclusion: Dyskinesia should be carefully monitored in patients undergoing LCIG, with particular caution for female patients. Whether combined clinical and pharmacodynamic assessments could be helpful to manage patients with troublesome dyskinesia under LCIG treatment needs further evaluation in a larger group of patients. Abstract : View Supplementary Video 1